On Income Inequality and Poverty in Egypt: Is Prosperity Immoral? - Lotfy Abdelkhalek, Mohamed Karim (AUC Knowledge Fountain, 2023)
There are varying perspectives on, and divergent solutions to, the phenomena of income inequality and poverty. There seems to be polarizing views on both of these sensitive topics. One side of the argument believes income inequality should in itself be mitigated through redistribution measures, while the other argues that this should not be the focus of policy makers, as it deters them from facing the more pressing issue facing society – which is absolute poverty. The relationship between income inequality, poverty, and citizen well-being in Egypt is one that warrants further research, and this paper aims to fill this lacuna. After analyzing the empirical data through quantitative tools, this paper shows that the relationship between these variables is rather blurred in the country, and that a decrease in Gini levels for instance are not necessarily a cause for celebration. Qualitative research was also conducted, and showcased that the sentiment of policy makers and policy influencers in Egypt was rather clear. Interviewees painted a vivid picture regarding the fact that income inequality should not be the focus of the government, rather the focus should be on absolute poverty – albeit through a multidimensional lens. There is indeed a massive effort in Egypt in order to drive down the poverty rates in the country, and these efforts have also been reflected upon in this research piece. However, there is room for additional measures, and this paper proceeds to provide a number of suggested policy tools that may help drive down these persistently high poverty rates in Egypt, rather than dwell on the incomes of the wealthy. Recommendations of this research are to 1) establish a national committee that is tasked with reducing multidimensional poverty in Egypt; 2) supplement income poverty with a multidimensional poverty index; 3) define equality of opportunity and then champion it across the board; 4) support primary economic sectors in Egypt; 5) heavily engage the private sector; 6) foster a culture of entrepreneurship; and 7) augment the labor force via including women.